Factors that influence the attitude of credit card users among government servants: the study of Jabatan Tenaga Kerja, Johor Bahru, Johor / Nadzirah R. Azmi and Nurhani Asyura Daud - R. Azmi, Nadzirah; Daud, Nurhani Asyura (Faculty of Business and Management, 2013)
The aim of this study is to determine the factors that influence the attitude of credit card users towards level of income, social interaction and financial institutions among government servantsat Jabatan Tenaga Kerja, Johor Bahru, Johor. The research instrument of this study is by distributing a questionnaire to the credit users among government servants at Jabatan Tenaga Kerja Johor Bahru, Johor. To analyze the data from the questionnaire that have been answered by respondents, we are using the Statistical Package for the Social Sciences (SPSS) version21.0. As result, the findings indicate that the most factors that influences the attitude of credit card user is financial institutions due the regression and correlation analysis result. This result by this study may valuable especially to the financial institution to more efficient and effectively on their management and aware about the implication toward credit card usage.